The Effect of Work-Family Conflict on Occupational Well-Being Among Primary and Secondary School Teachers: The Mediating Role of Psychological Capital - Mengmeng Zhou; Dawei Wang; Lianyong Zhou; Yiying Liu; Yixin Hu (Frontiers Media S.A., 2021)
In this study, 223 primary and secondary school teachers in Shandong province were selected to examine the effect of work-family conflict on occupational well-being, using the questionnaire of work-family conflict, occupational well-being and psychological capital as measuring instruments. We further explored the mediating role of psychological capital between work-family conflict and occupational well-being. The obtained data were analyzed using SPSS20.0, AMOS16.0 and M-plus 7.0. Results revealed that (1) Work-family conflict was negatively correlated with the occupational well-being and psychological capital of primary and secondary school teachers, and negatively predicted occupational well-being and psychological capital of primary and secondary school teachers; (2) Psychological capital had a significant positive correlation with the occupational well-being of primary and secondary school teachers, and significantly predicted the occupational well-being of primary and secondary school teachers; (3) Psychological capital of primary and secondary school teachers played a mediating role in work-family conflict and occupational well-being.